Two-Dimensional Scanning of Circularly Polarized Beams via Array-Fed Fabry–Perot Cavity Antennas - Mikhail Madji; Edoardo Negri; Walter Fuscaldo; Davide Comite; Alessandro Galli; Paolo Burghignoli (Applied Sciences)
In this paper, we present an array-fed Fabry–Perot cavity antenna (FPCA) based on a partially reflecting sheet (PRS) capable of generating a circularly polarized (CP), highly directive, far-field radiation pattern in the 27–28.5 GHz frequency range. The PRS, the cavity, and the array of feeders serve to different purposes in this original structure. The PRS is engineered to produce a circular polarization from a linearly polarized source placed inside the cavity. The cavity is optimized to obtain a directive conical beam from the dipole-like pattern of the simple source, and allows for a frequency scan of the beam along the elevation plane. The array of feeders is designed to obtain a pencil beam whose azimuthal pointing direction can be controlled by properly phasing the sources. The radiation performance is studied with a specific application of the reciprocity theorem in a full-wave solver along with the pattern multiplication principle. A number of array-pattern configurations in terms of operation frequency and phase shift are investigated and presented to show the potential of the proposed solution in terms of design flexibility and radiation performance.